Assessment of mold and yeast in some bakery products of Lahore, Pakistan based on LM and SEM. Issue 2 (18th November 2018) - Saeed, Iqra; Shaheen, Shabnum; Hussain, Khadim; Khan, Muhammad Asaf; Jaffer, Mehwish; Mahmood, Tariq; Khalid, Sana; Sarwar, Samina; Tahir, Arifa; Khan, Farah
Abstract: The present investigation was designed to throw light on the microbial status of bakery products available in bakeries and supermarkets of Lahore. Different bakery samples such as biscuits, pizza, patties were collected from different localities such as Anar Kali, Chauburji, Faisal Town, Iqbal Town, Model Town, Muslim Town were investigated for mold and yeast using serial dilution technique inoculated over malt extract agar and potato dextrose agar under sterilized conditions. Isolated fungi were namely Alternaria alternata, Aspergillus niger, Aspergillus flavus, Aspergillus fumigatus, Aspergillus terreus, Curvularia americana, Fusarium solani, Penicillium digitatum, Saccharomyces cerevisiae, and Geotrichum candidum . Results depicted maximum fungal viable count in biscuits, collected from Model Town while minimum count was in the samples of Chauburji. In the case of pizza, the maximum fungal viable count was found in the sample of Muslim Town. In the case of patties, the maximum fungal viable count was found in the sample of Muslim Town while minimum count was found in the sample of Iqbal Town. Prevalence of microorganisms may be due to the use of contaminated raw material, use of polluted waters, human handling, and the use of contaminated containers. Contaminated food intake can lead to measurable signs of liver injury, inflammation, etc. Preventive measures like washing and drying of hands before preparing food, cleaning of food preparation areas, and the use of clean equipment can avoid microbes which cause hazards to human health. Research Highlights: Bakery products of Lahore, Pakistan is investigated for the first time on the basis of light microscopy (LM) and scanning electron microscopy (SEM) and found very significant to check the quality of bakery products or not. Abstract :